It factors to (x+12)(x-12)
This is the same as (x-12)(x+12) as we can multiply two expressions in any order we want. This is like saying 7*5 is the same as 5*7
I used the difference of squares rule to factor x^2 - 144. It might help to write x^2 - 144 as x^2 - 12^2, then compare it to a^2 - b^2 = (a-b)(a+b)
Answer:
Step-by-step explanation:
Hint: 1 - Cos² A = Sin² A
Answer: x=12
Step-by-step explanation:
5x-15=2x+21(AIA)
3x-15=21
3x=36
x=12
Answer:
B
Step-by-step explanation:
B is in Quadrant III.
B is the answer.